Argo float observations of basin-scale deep convection in the Irminger sea during winter 2011-2012 - Piron, Anne; Thierry, Virginie; Mercier, Herle; Caniaux, Guy (Deep Sea Research Part I: Oceanographic Research Papers, 2016)
Analysis of Argo data obtained during winter 2011–2012 revealed the presence over the Irminger Basin of an exceptionally large number of profiles (41) with mixed layer depths (MLD) exceeding 700 m, which was deep enough to reach the pool of the intermediate Labrador Sea Water located in the Irminger Sea. Four of these profiles exhibited an MLD of 1000 m, which was the maximum value observed for the winter in question. The Argo sampling in the Irminger Sea during that winter, which was 3 to 4 times greater than for the preceding winters, enabled the different phases of the mixed layer deepening down to 1000 m, together with their spatial extents, to be observed for the first time. Two intense convective periods occurred: in late January south of Cape Farewell and in late February-early March east of Greenland. A final deepening period was observed in mid-March, during which the deepest mixed layers were observed. This long deepening period occurred in large regional areas and was followed by a rapid restratification phase. The temporal evolution of oxygen profiles from one Argo float testifies to the local and rapid ventilation of the mixed layer by the deep convection. A mixed layer heat budget along the trajectories of the 4 floats that sampled the deepest mixed layers showed that heat loss at the air-sea interface was mainly responsible for heat content variations in the mixed layer. Greenland Tip Jets were of primary importance for the development of deep convection in the Irminger Sea in the winter of 2011–2012. They enhanced the winter heat loss and two long (more than 24 hours), intense late events close together in time pushed the mixed layer deepening down to 1000 m. Net air-sea fluxes, the number of Greenland Tip Jets, the stratification of the water column, the NAO index and the Ekman-induced heat flux are pertinent indicators to assess conditions that are favorable for the development of deep convection in the Irminger Sea. By considering each of those indicators, it was concluded that the 2011-2012 ...